Hubungan Perilaku Merokok Dengan Kejadian TB Paru Di Puskesmas Plaosan Kecamatan Plaosan Kabupaten Magetan - Ilham Raka Kurniawan; Hanifah Ardiani; Retno Widiarini Widiarini (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2021)
ABSTRACTBackground: The number of tuberculosis cases in Plaosan Sub-District in 2016 was estimated 33 cases, in 2017 there were 42 cases and in 2018 there were 24 cases. This study aims to examine the relationship between smoking and the incidence of tuberculosis at the Plaosan Public Health Center in 2020.Methods: This type of research was quantitative with a case control design. The research sample was 52 respondent data from 2016-2018 with a ratio of 1: 3 for cases and controls. The sampling technique was Consecutive Sampling. The research data were obtained from secondary data available at Plaosan Public Health Center . Data analysis using Chi-Square Test.Results: The results of this study were in cases obtained 9 out of 13 (75.0%) respondents smoked and had pulmonary tuberculosis, while in control only 4 out of 39 (25.0%) respondents smoked. From the Chi-Square Test with a p value ≤ 0.001 and an OR value of 19.688 (95% CI 4.106- 94.402).Conclusion: There was a correlation between smoking behavior and the incidence of pulmonary tuberculosis in the Plaosan Public Health Center, Magetan Regency.Keywords: TBC, Lung TB, Smoking